A Multi-Pathogen Screening of Captive Reindeer (Rangifer tarandus) in Germany Based on Serological and Molecular Assays - Sánchez Romano, Javier; Grund, Lisa; Obiegala, Anna; Nymo, Ingebjørg H.; Ancin-Murguzur, Francisco Javier; Li, Hong; Król, Nina; Pfeffer, Martin; Tryland, Morten (Frontiers in Veterinary Science, 2019)
Captive reindeer in German zoos and wildlife parks live outside their natural geographic range and are exposed to a variety of viral, bacterial and protozoan pathogens, some host-specific and some which they are not exposed to in their native habitat. Reindeer blood samples and ticks collected in 2013 from 123 reindeer at 16 different zoological facilities were available from a previous study. The aims of this study were to assess the serological status of these animals with regards to various microorganisms as well as to test ticks (Ixodes ricinus) and blood samples for the presence of Anaplasma spp. DNA in order to evaluate the exposure of captive reindeer in Germany to a variety of pathogens. A total of 119 or 118 serum samples were screened (ELISA) and antibodies were detected (seropositive/tested, prevalence, confidence interval) against alphaherpesvirus (24/119, 20.3%, CI:13.9-28.3), bluetongue virus (BTV; 4/119, 3.4%, CI:1.0-8.7), malignant catarrhal fever related gammaherpesvirus (MCFV-related gammaherpesvirus; 7/119, 5.9%, CI:2.7-11.9), pestivirus (5/118, 4.2%, CI:1.6-9.8), Schmallenberg virus (SBV; 70/118, 59.3%, CI:50.3-67.8), smooth Brucella spp. (1/118; 0.9%, CI:0-5.1), Neospora caninum (5/118, 4.2%, CI:1.6-9.8) and Toxoplasma gondii (62/119, 52.1%, CI:43.2-60.9). These results suggested the exposure of reindeer to all tested pathogens. Moreover, real-time PCR for Anaplasma phagocytophilum targeting the partial msp2 gene was performed on DNA extracted from whole blood samples from reindeer (n=123) and from ticks (n=49) collected from 22 reindeer in seven different facilities. In addition to the real-time PCR, a semi-nested PCR for the partial groEL gene, and a nested PCR targeting the partial 16S rRNA gene were performed. DNA of A. phagocytophilum was detected in 17 reindeer (13.8%) and 15 ticks (30.6%). Three of the five reindeer with ticks having A. phagocytophilum DNA also had such DNA in blood. These results indicate that captive reindeer can be exposed to several ruminant pathogens that they hitherto had no known exposure to through their natural geographical distribution and habitats as shown for Culicoides-borne BTV and SBV. Further, captive reindeer may serve as reservoir hosts for pathogens circulating in local domestic, captive and wild ruminant species and populations and arthropod vectors.